A.R. Luria: Ideas and Prospects of Their Development in Pedagogical Psychology of the Twenty-first Century - Cheremisova, I (KnE Life Sciences, 2018)
A.R. Luria’s ideas are well-known and recognized both in Russia and abroad. Scientists from different countries are actively working in neuropsychology, a part of the psychological science developed by A.R. Luria. The author has shown the relevance and importance of the neuropsychological approach to the pedagogical psychology problems and the availability to choose an adequate educational and nurturing strategy from these standpoints. The study seeks to rethink and assess the importance of A.R. Luria’s main ideas from the modern pedagogical psychology’s standpoints. The characteristic of the main theoretical provisions has been set forth based on the analysis of A.R. Luria’s academic papers and the main directions and prospects for the development of A.R. Luria’s ideas in the modern psychological pedagogical science have been determined. A.R. Luria’s academic papers most sought by the modern researchers have been noted. The study is based on the materials of the thesis researches on the pedagogical psychology problems conducted in the beginning of the twenty-first century, A.R. Luria’s papers, the publications of other researchers who have studied his contribution to the psychological science. The study results show that A.R. Luria has significantly contributed to the development of the pedagogical psychology problems. A.R. Luria’s ideas on the interaction of the humanitarian and science knowledge in the human comprehensive study, the cultural and historical understanding of the psychical functions development, and the language evolution in the music language study for the musical education development seem most promising for the pedagogical psychology development. Note has been taken of the importance of A.R. Luria’s ideas for the elaboration of the relevant problems of the training and development of a person at any age; the study of individual and typical features in mastering a foreign language; the study of the semantics of speech and means of coding meanings in the context of professional training of psychologists and teachers, specialists in the field of artistic creativity. The analysis of A.R. Luria’s main ideas facilitates the deeper understanding of the modern problems of the pedagogical psychology theory and practice. Keywords: pedagogical psychology, A.R. Luria, musical education, professional training of psychologists, education in senior age, psychological service